Role of Bile Acids in Dysbiosis and Treatment of Nonalcoholic Fatty Liver Disease - Caihua Wang; Chunpeng Zhu; Liming Shao; Jun Ye; Yimin Shen; Yuezhong Ren (Mediators of Inflammation)
Nonalcoholic fatty liver disease (NAFLD) is a major health threat around the world and is characterized by dysbiosis. Primary bile acids are synthesized in the liver and converted into secondary bile acids by gut microbiota. Recent studies support the role of bile acids in modulating dysbiosis and NAFLD, while the mechanisms are not well elucidated. Dysbiosis may alter the size and the composition of the bile acid pool, resulting in reduced signaling of bile acid receptors such as farnesoid X receptor (FXR) and Takeda G protein-coupled receptor 5 (TGR5). These receptors are essential in lipid and glucose metabolism, and impaired bile acid signaling may cause NAFLD. Bile acids also reciprocally regulate the gut microbiota directly via antibacterial activity and indirectly via FXR. Therefore, bile acid signaling is closely linked to dysbiosis and NAFLD. During the past decade, stimulation of bile acid receptors with their agonists has been extensively explored for the treatment of NAFLD in both animal models and clinical trials. Early evidence has suggested the potential of bile acid receptor agonists in NAFLD management, but their long-term safety and effectiveness need further clarification.